1994
DOI: 10.1046/j.1469-0705.1994.04060505.x
|View full text |Cite
|
Sign up to set email alerts
|

Early sonographic diagnosis of intrapericardial teratoma

Abstract: An intrapericardial teratoma associated with a large pleural effusion and elevated aortic outflow velocity was diagnosed at 23.6 weeks' gestation. Less than 4 weeks earlier, an obstetric scan, including a four-chamber heart view, had been normal. In less than a week following diagnosis, fetal hydrops and bradycardia developed. 'Heroic' pericardiocentesis was declined by the patient, and the fetus died. This case demonstrates the potential for rapid growth in pericardial teratomas, and illustrates the possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…3,11,13 To the best of our knowledge, only 15 of the PTs reported in the English-language literature were diagnosed in utero ( Table 1). [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In those cases and the present case, the mothers ranged in age from 17 to 38 years (mean, 21 years; age not stated in 4 cases). The gestational age at which the tumors were sonographically detected ranged from 20 to 36 weeks (mean, 29 weeks).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…3,11,13 To the best of our knowledge, only 15 of the PTs reported in the English-language literature were diagnosed in utero ( Table 1). [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In those cases and the present case, the mothers ranged in age from 17 to 38 years (mean, 21 years; age not stated in 4 cases). The gestational age at which the tumors were sonographically detected ranged from 20 to 36 weeks (mean, 29 weeks).…”
Section: Discussionmentioning
confidence: 86%
“…Most of these cases were not reported in the radiologic literature, and the imaging features were not described in detail. [1][2][3][4][5][6][7][8][9][10][11][12][13][14]…”
mentioning
confidence: 99%
“…The median and interquartile range (IQR) for gestational age at diagnosis were 29.4 [25][26][27][28][29][30][31][32][33]. Of the liveborn infants (n = 24), the median for gestational age at delivery were 36.5 [IQR [32][33][34][35][36][37][38] weeks. Seven of 40 (29.2%) delivered vaginally; 13/40 (54.2%) had a cesarean section, and in 4 (16.7%) fetuses, the mode of delivery was not specified.…”
Section: Resultsmentioning
confidence: 99%
“…Intrapericardial teratomas have the potential to cause cardiac failure and hydrops fetalis, where the underlying mechanisms were proposed by Catanzarite et al [60] included: tamponade as a result of pericardial effusions, and direct tumor compression of the cardiovascular structures including the vena cava, aorta, and pulmonary artery. Ramírez et al [40] suggested that tumor compression of the heart and lung tissues was an alternative mechanism.…”
Section: Discussionmentioning
confidence: 99%